3 - Communal Governance and Transnationalism: A Case Study of the Nigerien Forex Trading Community in Benin City - Sambe, Martha; Olakpe, Oreva; Aliyu, Rafeeat (Africa Development, 2023)
Migrant community associations are well-structured and often engage in political transnationalism with their countries of origin. Nigerien migrants in Benin City, Edo State, occupy a dominant position in the unofficial foreign exchange market. Their communal governance structures reveal interesting parallels in the way the migrants govern themselves in relation to their status and the local nationals they work with. The politics within the migrant association suggest that, even in the absence of status, migrants are able to govern and protect their interests while contributing to the societies they find themselves in. This article looks at examples of Nigerien transnationalism in Nigeria at the micro level to reveal a complex network of communal governance. By studying the organisational lives of the Nigerien migrant community, we aim to understand how this group contributes to the maintenance f ties with Niger and enables their integration into their host community.